معنى الحياة و علاقته بقلق المستقبل و التحصيل الدراسي لدى الطلاب المعاقين جسدي ا في المرحلة الثانوية بمدينة الرياض - المناحي, عبد الله بن عبد العزيز مناحي (Journal of Faculty of Education, 2021)
The purpose of the study was to identify the relationship between the meaning of life dimensions and both future anxiety and academic achievement of students with physical )external / internal( disabilities. More specifically, it probed the differences in the meaning of life dimensions and academic achievement, and the predictability of both future anxiety and academic achievement based on the meaning of life dimensions. The sample consisted of 88 high school students with external )N = 44( and internal )N = 44( physical disabilities. No significant relationship was found between the total score of the meaning of life dimensions on one side and future anxiety and academic achievement of students with internal and external physical disabilities on the other side. Yet, statistically significant differences were detected between students with internal and external physical disabilities on the scale of the meaning of life dimensions and academic achievement. It was also revealed that future anxiety and achievement could be predicted by the meaning of life dimensions